The Implementation of Student Management in Fostering Religious Character of Students at SMP Muhammadiyah 7 Colomadu - Dinda Riska; Muhammad Wildan Shohib (Universitas Sarjanawiyata Tamansiswa, 2026)
The global shift toward holistic education has intensified scholarly attention on character education within religious-based institutions. This study examines how student management functions as a structural mechanism facilitating the internalization of religious values in Islamic secondary education. Employing a qualitative case study design, the research was conducted at an Islamic junior secondary school in Indonesia over a two-month period. Data were collected through prolonged observation, in-depth semi-structured interviews with school stakeholders responsible for student affairs and religious programs, and analysis of institutional documents. The data were analyzed thematically to identify patterns of religious character formation embedded in student management practices. The findings indicate that student management systematically shapes students’ religious behavior through structured routines, disciplinary regulations, and school-wide religious programs. These mechanisms effectively foster religious discipline and behavioral conformity; however, they show limitations in developing students’ reflective religious awareness. Differences in family-based religious support and increased exposure to digital environments emerge as significant challenges that weaken the sustainability of religious character beyond school supervision. Distinct from prior studies that predominantly emphasize curriculum and classroom-based instruction, this study demonstrates that student management operates as a moral regulatory system influencing students’ religious character in non-instructional spaces. The study underscores the importance for Islamic schools to adopt integrative student management strategies that balance habituation, reflective engagement, and religious digital literacy to support sustainable character development.